Self-Assessment of Students’ Role Play to Improve Speaking Skills - Salazar Zhunio, Olga Mariuxi (2023)
Nowadays, English is considered one of the global languages in the modern world. It has become an international and communicational language for business, science, technology, and travel. In the field of education, English is an important subject in public and private schools, and mastering it can help students have study opportunities abroad, increase their career opportunities, get a job in international companies, have a good salary, or meet people worldwide (Ministerio de Educación de Ecuador, 2016). As a result, most countries include English classes as part of their school syllabi, and students start them as soon as they turn six years old. In the case of Ecuador, the government designed an English curriculum in public schools for students in Educación General Básica (2nd to 10th) and Bachillerato General Unificado (1st to 3rd). This curriculum aims to support the policy of developing citizens that can effectively communicate in today’s globalized world (Ministerio de Educación de Ecuador, 2016). In other words, the main objective of this Ecuadorian English curriculum is to encourage learners to communicate and learn this foreign language. However, it is a reality that even though the government implemented this new curriculum to reach the B1 level of English proficiency in classrooms, the standards have not been accomplished yet (Paucar, 2016). According to the EF English Proficiency Index (EF EPI), “Ecuador continues to have a low level of English language proficiency” (Education First, 2022 p.1).